تقييم عملية الإبداع في الجزائر خلال الفترة 1996 - 2007 - الطيب، دويس محمد Altayeb, Duwais Mohammed; بختي، إبراهيم (جامعة قاصدي مرباح ورقلة, 2012)
تعتبر عملية تقييم الإبداع صعبة، نظرا لتداخل الفاعلين وقلة المعطيات الدقيقة التي تقيس مدخلاتها ومخرجاتها، وتبقى براءة الاختراع من بين الأدوات القليلة المتوفرة، والتي تسمح بإعطاء تقييم كمي ونوعي، جغرافي لعملية الإبداع في أي منطقة؛ لذا سنحاول من خلال هذا المقال واعتمادا على قاعدة معطيات براءات الاختراع في الجزائر، تحديد هوية المبدعين الجزائريين الذين حصلوا على براءات الاختراع، باستخدام عملية تصنيف لهم، بغية معرفة القطاعات والجهات التي تقوم بعملية الإبداع وتوزعهم الجغرافي وفق توزع النشاط الاقتصادي في البلاد، ومعرفة المجالات التكنولوجية التي تستقطب معظم المبدعين؛ وقد بينت أهم النتائج المتوصل إليها بأن معظم الإبداعات يقوم بها أفراد تليهم المؤسسات الاقتصادية الخاصة والعامة، وهو ما يعطي فكرة واضحة عن نوعية الإبداعات وطرق تمويلها، وهو ما يخالف الوضعية الموجودة في معظم الدول المتقدمة. Evaluating innovation is a difficult process, due to the actors’ interference and the lack of accurate data that measure its inputs and outputs. Accordingly, patent remains among the few available tools that enable quantitative and qualitative evaluation of innovation process in any area. Therefore, in this article and depending on the patents’ database of in Algeria, we will attempt to determine the Algerian innovators identities who have acquired patents. In addition, we try to classify them in order to find out which sectors and actors do innovation process and their geographic distribution according to the distribution of economic activity in the country, and to know the fields of technology that attract most of the innovators. The results have shown that most of the innovations are carried by the individuals followed by private and public economic institutions. This gives a clear idea about the quality of innovations and its financing in Algeria, which is contrary to the existing situation in most developed countries
Keywords: النقد الإبداعي -- براءة الاختراع -- تكنولوجيا المعلومات -- الجزائر -- حقوق الملكية الفكرية